The innovative way of cooperation between a large company and start-ups extends their survival period - Pompe, Andrej (Advances in business related scientific research journal, 2025)
Large enterprises seek collaboration with startup companies to gain agility, relevance, and a perception of being socially responsible. For startups, collaboration with large enterprises is extremely important, as on average only 10% of startups survive their first year. This collaboration helps them accelerate development, establish market presence, and improve survival rates. This article presents the brand Štartaj Slovenija, an innovative model of collaboration between a large enterprise and startup suppliers, based on social responsibility. This model supports the thesis that such collaboration ensures startups a faster market entry, longer survival, and greater long-term resilience, while allowing large enterprises to create competitive advantages and build a reputation as socially responsible companies. Štartaj Slovenija transcends traditional partnerships by additionally involving a marketing agency and a mass media outlet in the collaboration. The article also confirms that such innovative collaborations are not risky for large enterprises
Keywords: big enterprise; innovative cooperation and partnership; innovative networking; social responsibility; start-up company